2011
DOI: 10.2109/jcersj2.119.285
|View full text |Cite
|
Sign up to set email alerts
|

Cation distribution analysis of Sr-La-Co M-type ferrites by neutron diffraction, extended X-ray absorption fine structure and X-ray magnetic circular dichroism

Abstract: The occupation sites of lanthanum and cobalt ions in the LaCo substituted M type ferrite Sr 1¹x La x Co x Fe 11.6¹x O 19 , where x = 0.20 to 0.35, were analyzed by the neutron diffraction, the extended X-ray absorption fine structure (EXAFS) and the X-ray magnetic circular dichroism (XMCD) in order to understand the relationship between the local structure and the improvements of magnetic characteristics in the LaCo substituted M-type ferrite. The results of EXAFS analysis suggest that Co is partitioned in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 17 publications
0
17
0
3
Order By: Relevance
“…Recently, Kobayashi et al [5] claimed that Co occupies 4f 1 , 2a, and 12k sites from the results of x-ray absorption spectroscopy (XAS) combined with neutron diffraction Rietveld refinement analysis. In addition, they claimed from the results of hard x-ray magnetic circular dichroism (MCD) experiment that Co occupies the tetrahedrally coordinated, namely 4f 1 , site.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Kobayashi et al [5] claimed that Co occupies 4f 1 , 2a, and 12k sites from the results of x-ray absorption spectroscopy (XAS) combined with neutron diffraction Rietveld refinement analysis. In addition, they claimed from the results of hard x-ray magnetic circular dichroism (MCD) experiment that Co occupies the tetrahedrally coordinated, namely 4f 1 , site.…”
Section: Resultsmentioning
confidence: 99%
“…The improvement of the magnetic performance by the Co substitution is mainly ascribed to the increase in the coercivity, namely the enhancement in the uniaxial anisotropy associated with the unquenched orbital magnetic moment of Co 2+ occupying at particular Fe sites. In both Sr-La-Co and Ca-La-Co systems, Co tends to occupy more than two Fe sites [4][5][6][7]. It is likely, however, that Co at particular sites only contributes to the uniaxial anisotropy, while the other Co is useless or even harmful in enhancing magnetic performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been supported by Raman spectroscopy [4]. However, this argument was found to be in discordance with the conclusion obtained recently from simultaneous analyses of neutron diffraction and extended X-ray absorption fine structure (EXAFS) spectra, which excludes 4 f 2 and 2b sites as possible Co occupation sites [5]. Furthermore, in previous studies, Co occupation at the 4 f 1 site has actually been suggested from neutron diffraction [6] and NMR measurements [3].…”
Section: Introductionmentioning
confidence: 74%
“…Furthermore, in previous studies, Co occupation at the 4 f 1 site has actually been suggested from neutron diffraction [6] and NMR measurements [3]. X-ray magnetic circular dichroism (XMCD) measurements also indicated that Fe atoms at the 4 f 1 site are replaced by Co [5]. This discrepancy may originate in the site assignment in Mössbauer analyses, for example, incorrect assignment between 4 f 1 and 4 f 2 sites with the same atomic fraction.…”
Section: Introductionmentioning
confidence: 98%